1995
DOI: 10.1007/bf00278918
|View full text |Cite
|
Sign up to set email alerts
|

Variability of geometric measurements from three-dimensional reconstructions of scoliotic spines and rib cages

Abstract: Three-dimensional (3-D) reconstructions of the spine are being used with increasing frequency to describe scoliotic deformities, but the reproducibility of most of these techniques and the implication for the reliability of measurements made on the reconstructions has not been reported. How reliable are these reconstructions, and can a clinician interpret with confidence the results of studies based on such mathematical models? A reproducibility study of various computerised measurements obtained from 3-D reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 14 publications
1
34
0
1
Order By: Relevance
“…However, the fundamental limitation of visualizing the key anatomical landmarks still exists. Some studies reported inter and intra observer differences during measurements of sagittal spine curvatures [21][22][23]. The differences are due to the inherent anatomical variants that alters the normal spine symmetry from side-to-side [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fundamental limitation of visualizing the key anatomical landmarks still exists. Some studies reported inter and intra observer differences during measurements of sagittal spine curvatures [21][22][23]. The differences are due to the inherent anatomical variants that alters the normal spine symmetry from side-to-side [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the geometric parameters calculated from the 3D models has been shown to be smaller or within the inter-and intra-observer errors of similar clinical measurements made on radiographs with various rulers or goniometers [16].…”
Section: Methodsmentioning
confidence: 82%
“…Labelle et al [13] reported reliability of 1.1°for rib hump measured on rib cage 3-D reconstructions, based on repeated measures but not on repeated acquisitions. The reliability of the apparent rib hump index, based on back surface rotation, was comparable, with a typical error of measurement of 1.4°, considering that our results included the repositioning error.…”
Section: Differences Between the Two Posturesmentioning
confidence: 99%